The global prevalence of sexual disorder in patients with rheumatoid arthritis: a systematic review and meta-analysis - Salari, Nader; Hesampour, Arian; Abdolmaleki, Amir; Heidarian, Pegah; Shohaimi, Shamarina; Mohammadi, Masoud (Springer, 2024)
Rheumatoid arthritis (RA) is an autoimmune-associated pathology with an articular inflammatory basis. RA is diagnosed by severe pain, movement restriction, fatigue, anxiety, depression, and sexual disorder (SD). This pathology can potentially reduce the quality of life and cause many problems. The electronic databases of PubMed, Scopus, Web of Science, Embase, ScienceDirect, and Google Scholar search engine were systematically searched for the papers reporting the prevalence of SD in patients with RA (by August 2023). Following paper collection and data extraction, the Random Effects model was used to perform the data analysis (CMA, v.2). The heterogeneity of studies was assessed using I2 index. Following the assessment of 53 eligible studies with a sample size of 9,174 cases, the overall prevalence of SD in RA patients was 32.4% (95% CI:24.4–41.6). Also, the prevalence of SD in RA females and males was 36.5% (95% CI: 26.4–48) and 23.5% (95% CI:12.6–39.4), respectively. Based on the findings, the prevalence of SD among RA individuals was found relatively high; thus, the application of measures seems necessary to prevent sexual disorders in RA cases. These strategies are useful for health policymakers.